How Polling Trends Influence Compensational Coalition-Voting - Fredén, Annika (Frontiers in Political Science, 2021)
Compensational voting refers to when voters cast a vote for a more extreme party than they prefer, in order to push policies closer to an ideal point. This article develops the idea of compensational voting in regard to pre-electoral coalition signals and polling trends. The argument is that a significant share of voters consider the relative strength of the parties in their preferred pre-electoral coalition, and adjust their vote choice accordingly. This is elaborated by conducting a mixed logit model over eight Swedish general elections where parties were more or less clear about their intentions to collaborate with other parties. Combining unique data from parties’ election manifestos including negative and positive quotes about other parties with polling trends and voters’ approval rating of parties, the analysis lends support to the idea that this type of coalition-oriented compensational voting occurs.